Polyphenol-Rich Diets Exacerbate AMPK-Mediated Autophagy, Decreasing Proliferation of Mosquito Midgut Microbiota, and Extending Vector Lifespan - Nunes, Rodrigo Dutra; Ventura-Martins, Guilherme; Moretti, Débora Monteiro; Medeiros-Castro, Priscilla; Rocha-Santos, Carlucio; Daumas-Filho, Carlos Renato de Oliveira; Bittencourt-Cunha, Paula Rego Barros; Martins-Cardoso, Karina; Cudischevitch, Cecília Oliveira; Menna-Barreto, Rubem Figueiredo Sadok; Oliveira, José Henrique Maia; Gusmão, Desiely Silva; et al. (PLOS Neglected Tropical Diseases, 2016)
Author Summary The dramatic climate changes currently occurring on our planet may likely influence the biology and the distribution of mosquitoes. Aedes aegypti is a major vector of arboviruses. However, females feed on plants for a few days before feeding on blood for the first time. Plants are sessile and cannot move to search for better environmental conditions. In times of extreme temperatures, drought, or UV radiation plants produce polyphenols that allow plants to survive under such extreme conditions. Polyphenol ingestion by mosquitoes enhances the activity of an enzyme named AMP-activated protein kinase (AMPK). Mosquitoes emerging from pupae leave the aquatic environment and are readily colonized by many bacterial strains. Polyphenol-fed mosquitoes display a huge activation of AMPK which enhances autophagy in the midgut cells that increases the capture and killing of midgut bacteria, thus enhancing vector lifespan. Therefore, early meals on polyphenol sources allow for the regulation of vector microbiota. These data may provide the basis of a novel strategy that promotes bacterial proliferation and a shortening of vector lifespan.